An open-source GIS approach to understanding dunefield morphologic variability at Kati Thanda (Lake Eyre), Central Australia - Fischer, Lorenz M.; Sommer, Christian; Fitzsimmons, Kathryn E. (Frontiers in Earth Science, 2023)
Future climate projections indicate an expansion of the world’s drylands, and with that a commensurate increase in the mobilization of unconsolidated desert sediments such as sand and dust. It is therefore increasingly important to investigate the large-scale formation of dryland landscapes such as dunefields in order to better understand the processes responsible for their genesis, evolution, and thresholds for mobilization. Assessing dunefield morphologic variability, including analysis of the morphologic relationship between aeolian bedforms and other landforms such as fluvial channels and bedrock uplands, underpins such investigations. So far, however, meaningful investigations of erg-scale geomorphic patterns have been limited. This is in part due to the technological limitations of geographic information system (GIS) tools, particularly in the case of open-source datasets and software, which has effectively hindered investigations by colleagues in drylands of the global south where many of the world’s dunefields are located. Recent years have overseen the increasing availability of open-source remote sensing datasets, as well as the development of freely available software which can undertake geographic object-based image analysis (GEOBIA). These new tools facilitate cartography and statistical analysis of dunefields at large scales. In this study we make use of open-source GIS to characterise a morphologically diverse linear dunefield southwest of Kati Thanda (Lake Eyre) in central Australia. We focus on three parameters; dune orientation, spacing and Y-junctions using semi-automated GEOBIA, and investigate these in the context of local fluvial channels, depressions (pans) and uplands. Our results suggest a possible correlation between dune orientation, wind regime and the role of uplands as deflective barriers to longitudinal dune migration; dune spacing and sediment supply, likely relating to the location of both ephemeral and abandoned fluvial channels; and Y-junction frequency with underlying topography. Our study provides a framework for understanding process-based interactions between dunes and other landforms, as well as the first completely open-source approach which can be applied to linear dunefields worldwide.